Influence of microhábitat on the trophic ecology of two leptodactylids from northeastern Argentina. - Duré Pitteri, Marta Inés (2004)
We analyzed trophic ecology and its relationship with environmental variables for two leptodactylid species, Leptodactylus latinasus and L. bufonius (Anura: Leptodactylidae). The two species are common around Corrientes City, Argentina, where they live in the same habitat. The main objectives were to analyze the diets and patterns of coexistence relative to the microhabitat of each species. Weekly sampling was carried out January 1997–February 2000. A randomization test and canonical correspondence analysis (CCA) were used for data analysis. In L. latinasus, the diet was dominated numerically by isopterans and coleopterans (25.25% and 21.21%, respectively) and volumetrically by insect larvae (37.14%). In L. bufonius, the alimentary contents were dominated numerically by isopterans (60.49%) and volumetrically by coleopterans (62.47%). The trophic niche breadth was wider in L. latinasus (6.55) than L. bufonius (2.44). The overlap in the trophic niche (prey proportion) was higher (Ojk 5 0.81) and significantly greater than the expected mean value obtained by chance (0.27). Spatial niche overlap between the two species was low (Ojk 5 0.331) and not significantly different than the mean value expected by chance (0.52). Differences in microhabitat use were observed. While L. latinasus showed strong preference for mud, ground with crevices, and short grass and mud, L. bufonius showed preferences for dry land and short grass. In addition, the presence of this species was positively correlated with temperature and rainfall variables. Niche complementarity was observed between these species; although they exhibit high overlap in food, they tended to have low overlap in microhabitat use